IS PUBLIC DEBT NEUTRAL? EVIDENCES FOR INDONESIA - Arti Adji (Journal of Indonesian Economy and Business (JIEB), 1995)
"Jer basuki mawa bea". There is no such thing as a free lunch. Governmentlike other economic agents-has to finance its expenditures, now or later. "Oikosnomos",-Greek words from which the word economics came from is the essence ofgovernment activities in managing its budget. The topic of this paper concerns withthe way the government finances its budget and its effects on economic activity.Specifically, this paper is aimed to test empirically whether the Ricardianequivalence or a public debt neutrality holds in Indonesia. The longrun analysis of anerror correction representation suggests that the timing of taxation does not matter,implying that the government can conduct mix-finance fiscal policy. Furthermore,test for rationality conducted in this paper shows the evidence of rational consumersone of the assumptions underlying the Ricardian hypothesis to hold.